Presence and engagement on Instagram of NGOs for the elderly in Spain - Carrasco Polaino, Rafael; Pedreño Santos, Ana (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This research analyses the communication that Spanish NGO that focus their activity on helping older people carry out through the social network Instagram, in order to analyse the format, polarity and objectivity of the messages published and relate each one of these variables with the engagement generated. The analysis of 37,916 posts shows that there is greater engagement in images than in videos and in comments with a positive sentiment and objective character. The main conclusion is the need for development of the communication of these NGO on Instagram.